(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2023)
This issue contains scientific, professional papers and reviews written in a wide range of European languages, which introduces the authors and their work to the reader. The credit belongs to researchers and writers encompassing eight countries: Rossella Montibeler and Dejan Malčić from Bosnia and Herzegovina; Sevda Kaman, Şeyma Ebru Koca, Nur Kılıçaslan, Muhammed Durmaz and Turgay Kabak from Turkey; Jonida Cungu, Teuta Toska, Marsela Likaj and Ema Kristo from Albania; Danijela Kostadinović from the Republic of Serbia; Mihrije Maloku-Morina, Mirvan Xhemaili and Hysen Kasumi from Kosovo; Tatjana Vukelić from The Republic of Croatia; François Schmitt from The Slovac Republic; Andrea Frydrychová from The Czech Republic; Blerta Ceka, Gëzim Xhaferri, Biljana Ivanovska, Marija Stojanoska, Violeta Janusheva, Igor Stanojoski, Marija Gjorgjieva-Dimova, Sunchica Trifunovska Janikj, Petar Namichev, Ekaterina Namicheva-Todorovska, Anastazija Kirkova-Naskova, Ivana Duckinoska-Mihajlovska, Vesna Mojsova Chepishevska, Biljana Rajčinova-Nikolova, Ivan Antonovski and Lidija Kamceva Panova from Macedonia.